Taxonomic novelties in the fern genus Tectaria (Tectariaceae) - Ding, Hui-Hui; Chao, Yi-Shan; Dong, Shi-Yong (Phytotaxa, 2013)
The misapplication of the name Tectaria griffithii is corrected, which results in the revival of T. multicaudata and the proposal of a new combination (T. multicaudata var. amplissima) and two new synonyms (T. yunnanensis and T. multicaudata var. singaporeana). For the reduction of Psomiocarpa and Tectaridium (previously monotypic genera) into Tectaria, T. macleanii (new combination) and T. psomiocarpa (new name) are proposed as new combinations. In addition, the new name Tectaria subvariolosa is put forward to replace a later homonym (T. stenosemioides).